“Education enables us to take responsibility in our society”: an interview with Prof. Dr. Silke Hertel, Vice Rector for Student Affairs and Teaching, on future themes in teaching and learning (Heidelberg inspirations for innovative teaching, 2024)
Ein Interview mit Prof. Dr. Silke Hertel, Prorektorin für Studium und Lehre über zukünftige Themen des Lehrens und Lernens
Gesehen am 07.01.2025